Engels’s Theory of Social Murder and the Spectacle of Fascism: A Critical Enquiry into Digital Labour and its Alienation - Aishik Saha (tripleC: Communication, Capitalism & Critique)
In this paper, I shall attempt to respond to the charge that the digital labour theory, as developed by Christian Fuchs, doesn’t faithfully stick to the Marxist schema of the Labour Theory of Value by arguing that Marx’s critique of capitalism was based on the social and material cost of exploitation and the impact of capitalist exploitation of the working class. Engels’s analysis of The Condition of The Working Class in England links the various forms of violence faced by the working class to the bourgeois rule that props up their exploitation. I shall argue, within the framework of Critical Social Media Studies, that the rapid advance of fascist and authoritarian regimes represents a similar development of violence and dispossession, with digital capitalism being a major factor catalysing the rifts within societies. It shall be further argued that much like the exploitative nature of labour degrades social linkages and creates conditions that exaggerate social contradictions, the “labour” performed by social media users degenerates social relations and promotes a hyper-violent spectacle that aids and abets fascist and authoritarian regimes.